Identification and reassessment of the specific status of some tropical freshwater midges (Diptera: Chironomidae) using DNA barcode data - Pramual, Pairot; Simwisat, Kusumart; Martin, Jon (Zootaxa, 2016)
Chironomidae are a highly diverse group of insects. Members of this family are often included in programs monitoring the health of freshwater ecosystems. However, a difficulty in morphological identification, particularly of larval stages is the major obstacle to this application. In this study, we tested the efficiency of mitochondrial cytochrome c oxidase I (COI) sequences as the DNA barcoding region for species identification of Chironomidae in Thailand. The results revealed 14 species with a high success rate (>90%) for the correct species identification, which suggests the potential usefulness of the technique. However, some morphological species possess high (>3%) intraspecific genetic divergence that suggests these species could be species complexes and need further morphological or cytological examination. Sequence-based species delimitation analyses indicated that most specimens identified as Chironomus kiiensis, Tokunaga 1936, in Japan are conspecific with C. striatipennis, Kieffer 1912, although a small number form a separate cluster. A review of the descriptions of Kiefferulus tainanus (Kieffer 1912) and its junior synonym, K. biroi (Kieffer 1918), following our results, suggests that this synonymy is probably not correct and that K. tainanus occurs in Japan, China and Singapore, while K. biroi occurs in India and Thailand. Our results therefore revealed the usefulness of DNA barcoding for correct species identification of Chironomidae, particularly the immature stages. In addition, DNA barcodes could also uncover hidden diversity that can guide further taxonomic study, and offer a more efficient way to identify species than morphological analysis where large numbers of specimens are involved, provided the identifications of DNA barcodes in the databases are correct. Our studies indicate that this is not the case, and we identify cases of misidentifications for C. flaviplumus, Tokunaga 1940 and K. tainanus.